Caregiver burden experiences of caregivers of patients with schizophrenia: A qualitative inquiry - Kalayci, Erdinc; Uzunaslan, Imran; Uzunaslan, Serif (Sage Publications Ltd, 2023)
Background: Parents of children with schizophrenia struggle with emotional, social, and economic burdens because they do not receive adequate support and experience difficulties. Aim: To determine the caregiver burden experiences of parents who care for schizophrenic patients and to provide in-depth data on their feelings, thoughts, and opinions on this issue. Methods: In this study, the phenomenological method was used. In-depth interviews were conducted with 13 parents. Maxqda 2020 was used for the analysis of the research data. Results: In our qualitative study, it was concluded that caregivers were stigmatized by their environment, exposed to social isolation, and stigmatized themselves. It has been determined that the social isolation experienced by the parents negatively affects them economically, socially, and emotionally. Conclusion: The results of this study were discussed within the framework of three themes: emotional burden, social burden, and economic burden experienced by caregivers.
Keywords: Schizophrenia; caregiver; burden; qualitative method